The Rise of New Forms of Power in Africa: The Emergence of Big Men in the Afar Region of Ethiopia - Gemechu Adimassu Abeshu (Modern Africa, 2019)
This article chronicles the emergence of a new form of power in the Afar Region of Ethiopia. The Afar people are predominantly Muslim pastoralists who live in a territory referred to as the Afar-Triangle (located in Ethiopia, Djibouti and Eritrea). Fieldwork for this study was conducted on Dobi in the Afar Region of Ethiopia, the second largest salt mining site in Ethiopia. In 2004, Dobi fell under the control of an individual by the name of As Mohammed Humed Yayyo. This article focuses on this specific Big Man. Since his emergence, this Big Man became the sole power figure who grants access to mine salt on Dobi and who collects taxes. The nature of the relation between the Big Man and the Ethiopian State has been fluid and is characterised by collaboration and conflict.